# algebra

posted by .

Replace each equation with constants to complete the square and form a true equation
x^2+2x+--=(x+---)^2

• algebra -

how to do this: first, from the equation, we get b or the numerical coefficient of x.
from the given, b = 2.
then divide this by 2:
2/2 = 1
and square it:
1^2 = 1
thus, the number that we're looking for is 1:
x^2 + 2x + 1 =(x + 1)^2

hope this helps~ :)

## Similar Questions

1. ### math

1.Explain why there is no number that can replace N to make the equation |n| = -1 true. 2. List the integers that can replace N to make the statement -|8| < n < -|-5| true. I don't really get what am I supposed to do?
2. ### algebra

How do you complete the square by filling in the two blanks so as to produce a true equation. x^2 - 12x + ---- = (x - -----)^2

1. Reactions follow the law of conservation of mass. a.) True b.) False Answer: True 2. Reactants are the materials used in a chemical reaction. a.) True b.) False Answer: True 3. In a chemical equation, the mass on the left of the …
4. ### SAT algebra

(x-8)(x-k) = x^2-5kx+m In the equation above, k and m are constants. If the equation is true for all values of x, what is the value of m?
5. ### algebra

could you please check this answer for me and correct. thanks given equation point slope form linear equation to use to do question. y-3 = 3(x+1) question rewrite this equation in standard form y- 3 + 3 = 3x - 3x +3 + 3 -3x+ y = 6 …
6. ### Calculus

Complete the square to write the equation x^2 + y^2 - 6x - 2y + 4 = 0 in standard form. Use the standard form of the equation to identify the center and the radius of the circle.
7. ### algebra

If a line L1 has equation y = mx + b, where m and b are constants with m ¹ 0,then an equation of a line L2 perpendicular to L1 has the form , where C is a constant.
8. ### Algebra

Which of the following statements is true?
9. ### Algebra

True or False. If a line L1 has equation y = mx + b, where m and b are constants with m ‚ 0,then an equation of a line L2 perpendicular to L1 has the form , where C is a constant. L2: y= -1x +C
10. ### math

if the equation given is y^2-6y=24x+3, how do i out this equation into standard form, using complete the square as needed?

More Similar Questions